2022
DOI: 10.3390/nu14132692
|View full text |Cite
|
Sign up to set email alerts
|

Acute Effects of Cocoa Flavanols on Blood Pressure and Peripheral Vascular Reactivity in Type 2 Diabetes Mellitus and Essential Hypertension

Abstract: Background: Type 2 diabetes mellitus (T2DM) is associated with a high risk of vascular complications. Interestingly, cocoa flavanols (CF) can exert beneficial vascular effects in non-diabetic subjects. However, these effects have only been scarcely studied in T2DM. Therefore, we performed a study to assess the effects on vascular reactivity of a single dose of CF (790 mg) in T2DM and whether certain antihypertensive drugs may modulate these effects. Methods: 24 non-diabetic and 11 T2DM subjects were studied in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 75 publications
0
2
0
Order By: Relevance
“…Moreover, 200 mg daily of monomeric and oligomeric flavanols for three months on top of habitual diet and usual care did not reduce the plasma markers of endothelial dysfunction compared to the placebo in patients with long-term type 2 diabetes [197]. Finally, early this year, a crossover trial with type 2 diabetic (T2DM) and non-diabetic subjects that received 790 mg of cocoa flavanols daily reported that no beneficial effects of cocoa flavanols were detected on the vascular reactivity parameters in T2DM and non-diabetic participants [190].…”
Section: Recent Advances In Cocoa Flavanols In Cardiovascular Functionmentioning
confidence: 96%
See 1 more Smart Citation
“…Moreover, 200 mg daily of monomeric and oligomeric flavanols for three months on top of habitual diet and usual care did not reduce the plasma markers of endothelial dysfunction compared to the placebo in patients with long-term type 2 diabetes [197]. Finally, early this year, a crossover trial with type 2 diabetic (T2DM) and non-diabetic subjects that received 790 mg of cocoa flavanols daily reported that no beneficial effects of cocoa flavanols were detected on the vascular reactivity parameters in T2DM and non-diabetic participants [190].…”
Section: Recent Advances In Cocoa Flavanols In Cardiovascular Functionmentioning
confidence: 96%
“…Last year, a meta-analysis restricted to diabetic patients suggested that there is weak evidence for a reduction in diastolic but not systolic blood pressure after mid/long-term cocoa flavanol administration. These effects seem stronger in females, younger, and hypertensive when cocoa flavanols are ingested in one daily intake and when the epicatechin content is high enough [190].…”
Section: Recent Advances In Cocoa Flavanols In Cardiovascular Functionmentioning
confidence: 99%